Honrar o habitus, apagar os corpos: uma fofoca carnavalizante sobre a história do Doutor Honoris Causa nas faculdades de direito públicas do Brasil - Antônio Lopes de Almeida Neto (2023)
The general objective of the work is to analyze which bodies inhabit, or not, the memory and honor rolls of public Law schools in Brazil under the granting of the title of Doctor Honoris Causa. The universe of research chosen are the bachelors degree in Law from USP, UFPE, UFBA, UFRJ, UFMG, UFG, UFRGS, UFPA, UFC, Ufam, UFPR, UFSC, UFRN, UEPG, UFU, UESC, UnB, UNIMONTES, UFSM, Urca, UFCG UFRR and UFMS because of they being the most consolidated and prestigious spaces for research, teaching, extension and professionalization in the legal area. The approaches applied to all documents – publicly accessive in the digital collection of higher education institutions – are qualitative and quantitative. In order to distance the work from the logic of conventional investigations in the academic world, then, gossip was developed as a method. Such an epistemological movement is inspired by the idea of example and paradigm in Giorgio Agamben. Regarding the theoretical framework, the entire style and content on the body, the habitus, carnivalization, the state of exception and an-archy are based on the ideas of Friedrich Nietzsche, Mikhail Bakhtin, Walter Benjamin, Gilles Deleuze, Michel Foucault, Félix Guattari, Pierre Bourdieu, Antonio Negri, Luis Alberto Warat, Giorgio Agamben, Judith Butler, Michael Hardt, Emanuele Coccia and Andityas Matos. Regarding the result, the work comes to the conclusion that most of the bodies awarded the title of Doctor Honoris Causa by the academic units and approved by the respective University Councils are male, white, with a legal background and european, which reveals a device of exception inclusive-exclusive, structuring and structured, of the innumerable forms of knowledge and bodily gestures and in reading and writing before legal education and the university in general.